1994
DOI: 10.1111/j.1476-5381.1994.tb17131.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide receptors in human gastrointestinal epithelia

Abstract: Rat a-CGRP (0.2 nM) responses in HCA-7 epithelia were inhibited by the C-terminal fragment CGRP(8-37) (1 g.M). Pretreatment of Col-29 cells with CGRP(8-37) did not, however, alter the size or profile of responses to ra-CGRP (1 nM). 6 We conclude that high-affinity CGRP receptors exist on the basolateral surface of both cell lines, however they differ in their sensitivity to CGRP(8-37) and agonist orders of potency. Thus different CGRP receptor subtypes appear to predominate in these two epithelial cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
19
3
Order By: Relevance
“…The predominance of peptide receptors in the basolateral membranes of Col-6 monolayers was similar to, not only the sidedness seen for other agonists (MacVinish et al, 1993;Cox & Tough, 1994) in epithelial lines derived from the same parent cell line (Marsh et al, 1993) but also to the sidedness of NPY and PYY responses in jejunal and colonic mucosal preparations . Thus these cells can provide a useful model system for the study of peptide receptors in polarized epithelia in the absence of other mucosal cell types.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…The predominance of peptide receptors in the basolateral membranes of Col-6 monolayers was similar to, not only the sidedness seen for other agonists (MacVinish et al, 1993;Cox & Tough, 1994) in epithelial lines derived from the same parent cell line (Marsh et al, 1993) but also to the sidedness of NPY and PYY responses in jejunal and colonic mucosal preparations . Thus these cells can provide a useful model system for the study of peptide receptors in polarized epithelia in the absence of other mucosal cell types.…”
Section: Methodssupporting
confidence: 60%
“…Once confluent in culture flasks (25 cmn) epithelia were trypsinized (0.5% tryp~sin in versene, w/v) and seeded onto collagen-coated millipore filters as described previously (Cox & Tough, 1994). Cells covered the 0.2 cm2 area of filter within 10 days and once confluent, filters were used within 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…The behaviour of the Col-29 cells in this study stands in contrast to the CGRP 2 -like phenotype that we and others have previously found (Poyner et al, 1998;Cox & Tough, 1994). Perhaps signi®cantly there were dierences between the behaviour of the cells in the hands of Cox and Tough, who found that 3 mM CGRP 8-37 had no eect on the response to CGRP and ourselves, who found that this concentration was able to antagonize CGRP.…”
Section: Discussioncontrasting
confidence: 51%
“…Since we would expect the pK b value for CGRP in Col-29 cells to be at least one log unit lower than in SK-N-MC cells (Poyner et al, 1998), in this circumstance the CGRP receptor in these Col-29 cells could not be con®rmed as CGRP 2 . This result is contrary to published data (Cox & Tough, 1994) and indeed our own data (Poyner et al, 1998) ]a-CGRP was a more potent agonist in both cell types but there was only a 2 fold dierence between the two cell lines with an EC 50 of 67 nM in SK-N-MC cells and 152 nM in Col-29 cells ( Figure 1d). The similarity of responses with these agonists also suggests that the Col-29 cells used in this study have a CGRP 1 rather than CGRP 2 phenotype.…”
Section: Analysis Of Receptor Type In Sk-n-mc Rat-2 L6 and Col-29 Ccontrasting
confidence: 56%
“…Several hypotheses have been put forward. Species differences (rat atria vs guinea‐pig vas deferens) were proposed as an explanation for initial observations of heterogeneity; however, a spread of pA 2 values for CGRP 8–37 has since been observed in tissues from the same species and in discrete cell lines 33,43,45,46 . A range of other possibilities for the heterogeneity has also been suggested, including experimental artefacts, differential metabolism of antagonists, the use of non‐equilibrium conditions, problems of tissue accessibility and proteolysis.…”
Section: Non‐molecular Explanations For Cgrp Receptor Heterogeneitymentioning
confidence: 99%